2011
DOI: 10.1128/jcm.02373-10
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Molecular Characterization of Acinetobacter Clinical Isolates Obtained from Inmates of California Correctional Facilities

Abstract: Acinetobacter spp. increasingly have been wreaking havoc in hospitals and communities worldwide. Although much has been reported regarding Acinetobacter isolates responsible for nosocomial infections, little is known about these organisms in correctional facilities. In this study, we performed species identification, examined the antibiotic resistance profiles, and determined the mechanisms of resistance and clonal relationships of 123 Acinetobacter isolates obtained from inmates of 20 California correctional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 77 publications
5
20
0
Order By: Relevance
“…In other studies, PA␤N at 10 g/ml decreased the MIC values of chloramphenicol, clindamycin, and trimethoprim against clinical isolates regardless of the adeFGH expression status mostly 2-to 4-fold (552), while PA␤N at 20 g/ml reduced the nalidixic acid MIC up to 16-fold but displayed little effect on ciprofloxacin susceptibility (553). PA␤N and NMP, each at 100 g/ ml, restored susceptibility to fluoroquinolone (2-to 16-fold reduction of MICs) and tigecycline (mostly by a 2-fold MIC decrease) (554). Apparently, these EPIs have a stronger effect on resistance reversal with agents that have relatively high MIC values, such as chloramphenicol, clarithromycin, clindamycin, linezolid, rifampin, and trimethoprim (552,553,555), agents whose OM penetration is likely to be slow.…”
Section: Acinetobacter Sppmentioning
confidence: 98%
“…In other studies, PA␤N at 10 g/ml decreased the MIC values of chloramphenicol, clindamycin, and trimethoprim against clinical isolates regardless of the adeFGH expression status mostly 2-to 4-fold (552), while PA␤N at 20 g/ml reduced the nalidixic acid MIC up to 16-fold but displayed little effect on ciprofloxacin susceptibility (553). PA␤N and NMP, each at 100 g/ ml, restored susceptibility to fluoroquinolone (2-to 16-fold reduction of MICs) and tigecycline (mostly by a 2-fold MIC decrease) (554). Apparently, these EPIs have a stronger effect on resistance reversal with agents that have relatively high MIC values, such as chloramphenicol, clarithromycin, clindamycin, linezolid, rifampin, and trimethoprim (552,553,555), agents whose OM penetration is likely to be slow.…”
Section: Acinetobacter Sppmentioning
confidence: 98%
“…It was found that 16S-23S rRNA intergenic spacer sequences have a low degree of intra-species variation and high degrees of inter-species divergence. In another study [7], 28 types of strains, including 11 reference strains, were used; amplification and restriction of sequences was followed by DNA sequencing, revealing low-level similarity within the ACB complex. This study also demonstrated that internal transcribed spacer (ITS) sequences have better discriminatory power than a 16S rRNA gene.…”
Section: S-23s Rrna Intergenic Spacer Sequencesmentioning
confidence: 99%
“…Associated with the A. baumannii strain is a group of phenotypically and genetically closely related Gramnegative bacteria. These are non-motile, aerobic, rodshaped bacteria with polar fimbriae, which can have oxidase-negative and catalase-positive biochemical reactions [7,8]. These particular species have been named Acinetobacter calcoaceticus, Acinetobacter pittii (formerly referred to as the Acinetobacter genomic species 3), and Acinetobacter nosocomialis (formerly referred to as the Acinetobacter genomic species 13TU).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations